Inside the Sports Pages : Work Routines, Professional Ideologies, and the Manufacture of Sports News - Lowes, Mark Douglas, 1969- (Book collections on Project MUSE., 1999)
The working world of contemporary sports journalism through the eyes of the reporters, editors, and athletes who inhabit it. An account and analysis of the ideology behind sports news.